Strategic Culture and Weapons of Mass Destruction - Kartchner, K. author. aut Link
XX, 285 p.
Keywords: This book describes strategic culture and its value as a methodological approach to the study of International Relations. In particular, the book uses strategic culture to illuminate a number of case studies on countries that have made decisions regarding the acquisition, proliferation or use of weapons of mass destruction.